Multi-mode absorption spectroscopy using a quantum cascade laser for simultaneous detection of NO and H(2)O - O’Hagan, S. (Appl Phys B, 2016)
Detection of multiple transitions in NO and H(2)O using multi-mode absorption spectroscopy, MUMAS, with a quantum cascade laser, QCL, operating at 5.3 μm at scan rates up to 10 kHz is reported. The linewidth of longitudinal modes of the QCL is derived from pressure-dependent fits to experimental MUMAS data. Variations in the spectral structure of the broadband, multi-mode, output of the commercially available QCL employed are analysed to provide accurate fits of modelled MUMAS signatures to the experimental data.